Foetal Mummification in Pregnant Dairy Cows Induces Variant Changes on the Hormonal Profile, Biochemical Parameters and Mineral Profile of the Dam - Yahia A. Amin; Obeid Shanab; Ibrahim S. Zahran; Foad Farrag; Mariam A. Fawy; Mustafa Shukry; Mohamed Abdelmegeid; Eman M. Abu El‐Naga; Ragab H. Mohamed; Ahmed A. Elolimy (Veterinary Medicine and Science)
ABSTRACT Background and aim Foetal mummification does not cause loss by losing foetus only but the harm extends to the mother dam. This is the first study that investigates the changes that occur in the dam's body due to foetal mummification through a comprehensive investigation of the hormonal, biochemical, liver, kidney and mineral profiles of the dam. This study represents a model to investigate the pathogenesis of such clinically severe cases. Materials and methods This study involved 40 cows with foetal mummification. The dams were divided into 2 groups (20 for each): Group 1 (cows carrying normal foetuses [CNF]) and Group 2 (cows carrying mummified foetuses [CMF]). Blood samples were collected for evaluation of hormonal profile, biochemical profile, kidney profile, liver profile and mineral profile. Results Results showed that progesterone (P4) and oestradiol (E2) concentrations were not significantly changed in the CMF group compared to the CNF group, whereas total triiodothyronine (T3) and total thyroxin (T4) showed a significant reduction in mummified cases than in CNF group. In the CMF group, parameters such as glucose and albumin were significantly lower compared to the normal pregnant animals. In contrast, triglycerides, cholesterol, globulin and total protein (TP) were significantly higher. Kidney and liver profiles showed a significant increase in urea, aspartate aminotransferase (AST), alkaline phosphatase (ALP) and bilirubin, a significant decrease in alanine aminotransferase (ALT) and non‐significant differences in creatinine and gamma‐glutamyl transpeptidase (GGT) in CMF compared with normal pregnant cows. Mineral profiles showed a significant decrease in calcium and phosphorus, a significant increase in iron and potassium and a non‐significant increase in magnesium, sodium and chloride in the mummified group compared to the normal pregnancy group. Conclusion Cows with mummified foetuses (MF) maintained variant biological changes in the body. These findings can be used as an indicator for cow health and as a diagnostic tool to avoid pregnancy disorders that occur during the late pregnancy.